The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2478/v10086-011-0032-5
|View full text |Cite
|
Sign up to set email alerts
|

Marking and return method for evaluating the effects of stocking larval vendace, Coregonus albula (L.), into Lake Wigry in 2000-2001

Abstract: Abstract. In 2000 and 2001, larval vendace, Coregonus albula (L.), were marked and released into Lake Wigry. The larvae were immersed in alizarin red S. Of the 19.2 million vendace larvae released in 2000, 2 million were marked (10.4% of the overall number of fish released), and in 2001 of the 18.8 million fish released, 7 million were marked (47.8%). In subsequent years, otoliths were excised from caught vendace and the number of them with alizarin marks was determined. It was assumed that all unmarked specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…(), Poczyczyński et al . () and Eckmann et al . (), but the latter concluded that strong natural recruitment in the year of enhancement stocking has caused the low efficiency of the stocking measure.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…(), Poczyczyński et al . () and Eckmann et al . (), but the latter concluded that strong natural recruitment in the year of enhancement stocking has caused the low efficiency of the stocking measure.…”
Section: Discussionmentioning
confidence: 91%
“…Among the few studies on vendace enhancement stocking, such a high contribution of hatchery fish has only been shown by Poczyczyński et al . (), whereas Eckmann et al . () and Mehner et al .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This low-stress method (Lagardere et al 2000;Ibanez et al 2013) is particularly suitable for small fishes or those at an early life stage (Alcobendas et al 1991). Combined with stocking operations, mass marking by bath has provided an effective way to acquire knowledge about life history and to evaluate the results of management programmes on eel species (Meunier 1994;Verreault et al 2010;Desprez et al 2013; Wickstr€ om & Sj€ oberg 2013), or other fishes (Baer & R€ osch 2008;Caudron & Champigneulle 2009;Poczyczynski et al 2011). Combined with stocking operations, mass marking by bath has provided an effective way to acquire knowledge about life history and to evaluate the results of management programmes on eel species (Meunier 1994;Verreault et al 2010;Desprez et al 2013; Wickstr€ om & Sj€ oberg 2013), or other fishes (Baer & R€ osch 2008;Caudron & Champigneulle 2009;Poczyczynski et al 2011).…”
Section: Introductionmentioning
confidence: 99%